Dermoscopic Characteristics of Cutaneous Lupus Erythematosus According to Subtype, Lesion Location, Lesion Duration, and CLASI Score - Yıldız Gürsel Ürün; Mustafa Ürün; Mehmet Şerif Danışman (Dermatology Practical & Conceptual, 2024)
Introduction: Dermoscopic findings are used to diagnose and evaluate disease activity in patients with cutaneous lupus erythematosus (CLE).